EVALUATION OF ROAD MARKINGS RETOREFLECTION MEASURING METHODS - Darko Babic; Mario Fiolic; Petar Prusa (European Scientific Journal, ESJ, 2014)
Modern traffic demands the safe movement of vehicles under normal conditions and especially at night and in reduced visibility (fog, rain, sleet, etc.). Quality and quantity of participants visual guidance in traffic directly depends on the visibility and the reflective properties of road markings are of crucial importance. Using the latest methods and procedures of testing road markings a high and constant quality level can be achieved, and thus the security level of individual roads can be raised.. One of the most important elements for testing the quality of road markings is testing day and night visibility of road markings. These tests can be done in two ways: method for static test of road markings reflection (daytime and night-time visibility) and dynamic method for testing retroreflection of road markings (night-time visibility). Aim of this article is to describe and evaluate mentioned methods for measuring retroreflection of road markings.